THE DIAMETERS OF THE CIRCLE OF WILLIS ARTERIES IN A ROMANIAN POPULATION AND THEIR SIGNIFICANCE IN CEREBROVASCULAR DISEASES - Ana-Maria Dumitrescu; Claudia Florida Costea; Anca Sava; Lucia Corina Dima-Cozma; Laura Mihaela Trandafir; Doriana Agop Forna (Romanian Society of Oral Rehabilitation, 2024)
The aim of this study was to evaluate the the measurements of the circle of Willis (CW) arteries diameters in a Romanian population. Material and methods: We performed a retrospective study on a sample of 221 adult patients (≥18 years-old), hospitalized in the Emergency Clinical Hospital "Prof. Dr. N. Oblu" from Iași, Romania, over a period of 12 years, who died during hospitalization and on whom an autopsy was performed. Demographic data (age, gender, residence), causes of death and the outer diameters of CW constituent arteries were collected. There were 221 subjects, who were divided into four groups, according to the association of patient's cause of death with the presence of anatomical variants of CW. 76.01% of all subjects presented cerebrovascular disease (CVDs) and anatomical variant of the CW, thus representing the great majority. Patients "with CVDs and anatomical variants of CW" were older with about 4 years compared to the other three categories of patients, having an average age of 64.17 ±14.22 years. 56.3% of those "without CVDs and with anatomical variant of CW" and 62.5% of those patients deceased "with CVDs and anatomical variants of CW" had rural residences. 68.8% of all cases "without CVDs, but with anatomical variants of CW" were female patients. 37.5% of the patients "with CVDs and anatomical variants of CW" and 43.8% of the patients "without CVDs, but with anatomical variants of CW" lived in the urban environment. Statistically significant differences were observed between the mean outer diameters of the arteries of CW and the patient's cause of death (p <.001) in case of anterior communicating artery (AcoA), right anterior cerebral artery (ACA), right and left posterior communicating arteries (PcoAs), and right posterior cerebral artery (PCA). The smallest external diameters of ACoA, right ACA and left PcoA were identified in patients "with CVDs and anatomical variants of CW". Our research has provided evidence that a smaller diameter of the right ACA and left PcoA are associated with the occurrence of cerebrovascular diseases.